The Effect of Work Environment on Employee Performance at Fairfield By Marriott Bali Legian Hotel - Sitha Mahadewi, Anak Agung Istri; Diwyarthi, Ni Desak Made Santi; Sabudi, I Nyoman Sukana (Journal of Hotel Management, 2024)
A good work environment can make a positive contribution to employee performance, while a poor work environment can reduce employee performance. The background of the employee performance appraisal at Fairfield Hotel where there are still several employees who are on the performance appraisal scale with the underperformer category in the performance appraisal in 2023. So that the purpose of this study is to determine the effect of the work environment on employee performance at the Fairfield Hotel. The number of samples in this study were 51 respondents using the saturated sampling method. Data was collected by distributing questionnaires using a 5-point Likert scale to measure 27 statement items. The data analysis technique used is simple linear regression analysis, t-test, and coefficient of determination analysis which is processed with the SPSS version 29 for Windows program. The results of this study indicate that the work environment (X) has a positive and significant effect on employee performance (Y) at Fairfield Hotel. The T test results show the value of tcount> ttable, namely 4.654> 1.676 and a significance value of 0.002 <0.05, which means rejecting H0 or Ha is accepted. contributes to employee performance by 63.9%, while the remaining 36.1% is influenced by other variables not used in this study.